2000
DOI: 10.1176/appi.ajp.157.9.1416
|View full text |Cite
|
Sign up to set email alerts
|

Attention, Memory, and Motor Skills as Childhood Predictors of Schizophrenia-Related Psychoses: The New York High-Risk Project

Abstract: Schizophrenia-related psychoses in adulthood are distinguished in subjects at risk for schizophrenia by childhood deficits in verbal memory, gross motor skills, and attention. The findings suggest that deficits in these variables are relatively specific to schizophrenia risk and may be indicators of the genetic liability to schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
258
0
15

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 451 publications
(293 citation statements)
references
References 31 publications
18
258
0
15
Order By: Relevance
“…The earliest developmental research of risk markers involved the follow-up of high-risk samples, and most studies showing some persistence of risk markers are high-risk studies (Watt, 1978;Marcus et al, 1993;Erlenmeyer-Kimling et al, 2000). Our results support the hypothesis that in an unselected sample the persistence of developmental delay is independent of known genetic risk of psychoses.…”
supporting
confidence: 75%
See 1 more Smart Citation
“…The earliest developmental research of risk markers involved the follow-up of high-risk samples, and most studies showing some persistence of risk markers are high-risk studies (Watt, 1978;Marcus et al, 1993;Erlenmeyer-Kimling et al, 2000). Our results support the hypothesis that in an unselected sample the persistence of developmental delay is independent of known genetic risk of psychoses.…”
supporting
confidence: 75%
“…Some evidence of persistence in deviant neuromotor development in high-risk infants has been reported 6 in motor skills (Mednick and Schulsinger, 1974), or having high frequencies of soft neurological signs (motor coordination and left-right orientation) during infancy and school age (Marcus et al, 1993). In the New York High-Risk Project, longitudinal stability and persistence was seen in verbal memory, gross motor function and attention (Erlenmeyer-Kimling et al, 2000). However, some studies show normal neurological development in high-risk infants (reviewed by Marcuse and Cornblatt 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Working memory is also deficient among first-degree relatives of schizophrenia probands, as detected with both verbal (80) and spatial tasks (81). The New York High Risk Study reported that childhood scores on a verbal working memory factor successfully predicted later schizophrenia-spectrum psychoses among offspring of schizophrenia mothers, further supporting its relevance as an endophenotype for schizophrenia (82).…”
Section: Neurocognitive Endophenotypesmentioning
confidence: 96%
“…71 Attention deficit, abnormal gross motor skills, problems with verbal memory, late walking, and tendency to play alone have been regarded as possible indicators of schizophrenia. 2,3 Eating disorders (anorexia nervosa and bulimia nervosa)…”
Section: Schizophreniamentioning
confidence: 99%
“…1 Some psychiatric disorders such as schizophrenia are noticed before their most evident symptoms through changes in behavior and development during childhood or adolescence. 2,3 The DSM-IV (Diagnostic and Statistic Manual of Mental Disorders fourth edition text revision) presents more than 250 conditions that may co-occur with behavioral disorders. 4 The detection of the first symptoms of behavioral disorders allows the referral of patients to different p r o f e s s i o n a l s , w h e n e v e r n e c e s s a r y , f o r e a r l y interventions that could change the course of the disease.…”
Section: Introductionmentioning
confidence: 99%